2011
DOI: 10.1128/aem.01116-10
|View full text |Cite
|
Sign up to set email alerts
|

The Cell Membrane as a Major Site of Damage during Aerosolization of Escherichia coli

Abstract: This study aimed to provide data on the survival and site of damage of Escherichia coli cells following aerosolization using two different techniques, nebulization and flow focusing. Four metabolic stains were assessed for their ability to detect respiratory activities and membrane homeostasis in aerosolized E. coli cells. The degree of sublethal injury increased significantly over the 10-min period of aerosolization in E. coli cells aerosolized by using the Collison nebulizer, reaching up to 99.9% of the popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…It was found in our earlier study that the viability of P. fluorescens bacteria aerosolized by a Collison nebulizer (BGI Inc., Waltham, MA) decreased by over 50% after 90 min of continuous aerosolization (23). Similarly, Thomas et al indicated that 99.9% of an Escherichia coli population suffered sublethal injury after a 10-min aerosolization by a Collison nebulizer (24). They also concluded that the cell membrane was the major site of damage due to impaction and shear force stress that disturbed membrane homeostasis (24).…”
mentioning
confidence: 96%
“…It was found in our earlier study that the viability of P. fluorescens bacteria aerosolized by a Collison nebulizer (BGI Inc., Waltham, MA) decreased by over 50% after 90 min of continuous aerosolization (23). Similarly, Thomas et al indicated that 99.9% of an Escherichia coli population suffered sublethal injury after a 10-min aerosolization by a Collison nebulizer (24). They also concluded that the cell membrane was the major site of damage due to impaction and shear force stress that disturbed membrane homeostasis (24).…”
mentioning
confidence: 96%
“…Although the aerobiological stability characteristics of several species of Gramnegative bacteria already have been investigated, including S. marcescens (7,8,17,18), E. coli (19)(20)(21)(22)(23)(24)(25), and P. agglomerans (6,12,(26)(27)(28)(29)(30), most of these studies were performed more than 3 decades ago; thus, several knowledge gaps still remain. An inherent challenge regarding the aerobiological stability of Gram-negative bacteria is the observation that few generalizations seem to be applicable, suggesting that different genera, species, and even strains of Gram-negative bacteria have to be considered separate entities regarding their stability characteristics (11,15,16).…”
Section: Single-cell Particles and Cell Clusters Produced From Differmentioning
confidence: 99%
“…It also could be interesting to study several strains of the same bacterial species to specifically address strain-specific aerobiological stability characteristics. The ambition for the future also involves adopting additional characterization methods, including flow cytometry in combination with membrane integrity and metabolic cell staining (20,45,46) and quantitative PCR in combination with ethidium or propidium monoazide live-dead discrimination techniques (47)(48)(49)(50), as well as the study of multiple strains of the same bacterial species to investigate strain-specific aerobiological stability characteristics.…”
Section: Single-cell Particles and Cell Clusters Produced From Differmentioning
confidence: 99%
“…Direct phase contrast and fluorescence microscopy (Hernandez et al, 1999) showed these bacteria remained intact after inspecting nebulizer reflux immediately following their aerosolization. Based on previous studies with many of the same bacterial models used here, some microbes, particularly Gram negative bacteria harvested in their log growth phase, can experience significant viability losses after being refluxed in Collison nebulizers even after 10 min (Stone and Johnson, 2002;Thomas et al, 2011). To minimize aerosolization stress and viability variance, bacterial cultures were harvested in early stationary phase, and nebulization times were limited to 2 min.…”
Section: Bacteriamentioning
confidence: 99%